Fortuitous enchondroma of hand in a traumatic fracture: a case report of Ollier’s disease - Krishnappa, Santosh Kumar; R. L., Ramesh; Vemgal, Prakash (International Journal of Contemporary Pediatrics, 2017)
Enchondromas are benign cartilage forming tumors most commonly involving the marrow cavity of the long bones. Ollier disease is one of the subtypes of Enchondromatosis associated with lesions in the center of the bone. Most commonly presenting in 2nd and 3rd decade of life. Radiological evidence is adequate for the diagnosis. Exact etiology is unknown with increasing genetic predilection. Regular follow up with conservative management remains the mainstay of treatment.